2019
DOI: 10.3390/nu11061305
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient Intake in Soccer Players—A Meta-Analysis

Abstract: The nutrition of soccer players is an important topic and its knowledge may help to increase the quality of this popular game and prevent possible health problems and injuries in players. This meta-analysis aims to estimate the current dietary trends of three basic macronutrients in junior and senior soccer players during the first two decades of the 21st century. We analyzed data from 647 junior players (mean age 10.0–19.3) from 27 groups, and 277 senior (mean age 20.7–27.1) players from 8 groups from altoget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 73 publications
4
40
1
2
Order By: Relevance
“…is nding is in agreement with a meta-analysis performed by Ste et al [36] regarding the macronutrient intake of soccer players. e authors suggested that soccer players may restrict carbohydrate as a consequence of warnings about carbohydrates overuse in the general population.…”
Section: Discussionsupporting
confidence: 92%
“…is nding is in agreement with a meta-analysis performed by Ste et al [36] regarding the macronutrient intake of soccer players. e authors suggested that soccer players may restrict carbohydrate as a consequence of warnings about carbohydrates overuse in the general population.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Kerksick et al [ 16 ] suggest that football players’ protein needs range from 1.2 to 1.4 g/kg body mass/day of high quality protein and might be increased to 2.0 g/kg body mass/day for short periods of intensive training, especially during the preparatory period. Current reports indicate that a protein intake above 1.7 g/kg body mass/day does not have a significant impact on the rate of muscle fiber regeneration in the post-workout period, nor will it improve myofibrillar synthesis [ 3 , 36 ]. Having this information in mind, the consumption of doses higher than 2.0 g/kg body mass/day is not required, especially when the athletes have long workouts and the breaks between meals are short, which makes it difficult to consume larger food portions.…”
Section: Discussionmentioning
confidence: 99%
“…Football players use both anaerobic and aerobic systems to fuel performance. Therefore, players depending on the nature of training, match-playing, and periods of training, will have unique energy demands and nutrient requirements [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that athletes who are hydrated can perform better than dehydrated ones (Kiitam et al, 2018). Cooperation between athletes, parents, coaches and sports dieticians is required to do an efficient nutritional program (Steffl, Kinkorova, Kokstejn, & Petr, 2019).…”
Section: Discussionmentioning
confidence: 99%